دور الزكاة في تحقيق العدالة الاجتماعية في الاقتصاد الإسلامي: The Role of Zakat in Realizing Social Justice in Islamic Economics - Amrulloh, Irsyad (Universitas Muhammadiyah Surakarta, 2025)
This research aims to explain the role of zakat in realizing social justice in the Islamic economic system, by highlighting the philosophy of legislation and its practical function in redistributing wealth and reducing social class gaps. This research begins with the basis of shari'i from the concept of justice, as stated in the Qur'an and hadith, emphasizing that zakat is required to achieve a great social goal, namely preventing the hoarding of wealth that only circulates among the rich, and ensuring the distribution of financial rights to those in need in society. This study uses an analytical descriptive approach, by discussing zakat fiqh related to the definition of justice, the law of zakat obligations, its types, various assets subject to zakat, and eight recipients of zakat, while showing legislative accuracy and economic justice that pays attention to differences in sources of wealth and difficulties in obtaining it. This research also discusses aspects of distributing zakat to the poor, people in debt, travelers, and in the way of Allah, and explains its impact in reducing the burden of life, paying off debts, maintaining human dignity, and strengthening the spirit of togetherness and social solidarity. This study also examines contemporary conditions through economic and social models and statistics, especially in Indonesian society, highlighting the great potential of zakat in overcoming poverty and unemployment, supporting education, and reducing economic inequality, if zakat institutions are properly functioned and their collection and distribution are carried out in accordance with sharia objectives. This study concludes that zakat is not only a financial worship, but a comprehensive social and economic system, which contributes to the realization of social justice, social stability, and sustainable development in Islamic society.